1998
DOI: 10.1097/00004728-199803000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer: Evaluation of Triphasic Spiral CT and Radiologic-Pathologic Correlation

Abstract: Spiral CT with triphasic scan technique improved the accuracy of estimating the depth of tumor invasion in advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 16 publications
3
39
1
4
Order By: Relevance
“…The cN-pN concordance rate in our data was 61.7 %, and it has been reported as 59-87 % in previous studies [11,[31][32][33][34]. These results imply a limitation to the diagnosis of LN metastasis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The cN-pN concordance rate in our data was 61.7 %, and it has been reported as 59-87 % in previous studies [11,[31][32][33][34]. These results imply a limitation to the diagnosis of LN metastasis.…”
Section: Discussionsupporting
confidence: 62%
“…In studies based on MDCT, the concordance between cT and pT was reported to be 76-89 % [11,[31][32][33][34]; however, the number of participants in these studies was small, ranging from 50 to 108, making the conclusions unreliable. Furthermore, the reports differed in the classification methods and the number of categories for cancer depth, making a generalized comparison impossible.…”
Section: Discussionmentioning
confidence: 97%
“…The third limitation of this study was that we did not obtain the gastric mucosal phase. The layered pattern of the normal gastric wall and early gastric cancer can be depicted clearly in the gastric mucosal phase [24,25]. It is useful for identifying the enhancement pattern of early gastric cancer [24] and for determining the depth of tumour invasion [25].…”
Section: H J Kim D H Lee and Y T Komentioning
confidence: 99%
“…The layered pattern of the normal gastric wall and early gastric cancer can be depicted clearly in the gastric mucosal phase [24,25]. It is useful for identifying the enhancement pattern of early gastric cancer [24] and for determining the depth of tumour invasion [25]. It also may be useful for tumour detection, especially for those tumours without obvious gastric wall thickening [8].…”
Section: H J Kim D H Lee and Y T Komentioning
confidence: 99%
“…However, the accuracy of establishing the N category is still poor ; 63 -78 using EUS [5][6][7][8][9][10][11] and 51 -78 using CT 9,[12][13][14][15][16][17][18] . The N category estimates 5-year survival rate in patients with N0 gastric cancer as 89.4 , but 68.3 in those with N1 disease 19 .…”
mentioning
confidence: 99%